PENYUSUNAN INSTRUMEN ASESMEN MINAT DAN GAYA BELAJAR ANAK DI KABUPATEN MAJENE - Saodi, Syamsuardi; Hiola, St. Fatmah; Ahmad, Muh. Ihsan Said; Hajerah, Hajerah; Hasmawaty, Hasmawaty (Kreasi: Jurnal Pengabdian Masyarakat, 2024)
Community Partnership Program (PKM): Training on the preparation of assessment instruments for children's interests and learning styles for teachers in kindergartens in Majene Regency, aims to improve the competence and basic ability of teachers in mastering assessments in education units, especially in kindergartens. This PKM will be held from April to November 2023 in Majene Regency, West Sulawesi with partners of the Indonesian Kindergarten Teachers Association (IGTKI) Banggae Branch, Majene Regency, West Sulawesi. PKM participants consist of teachers and principals of PAUD units. The methods used in this PKM activity are lectures, discussions, questions and answers and assignments. Analysis of the success rate of PKM activities is through measuring the level of mastery of the material and task completion. The final condition of the implementation of this Community Partnership Program activity shows that participants can understand how to prepare a Diagnostic Assessment on aspects of children's readiness and interest in learning in kindergarten. The success of this PKM can be seen from the high participation and motivation and discipline of participants during the training activities.